Teaching aids for dyslexia children a Multi-Sensory Approach / Norarifah Ali...[et al.] - Ali, Norarifah; Ahmad Sayuti, Nurul ‘Ayn; Azizan, Hasnul Azwan; Zainal@Ismail, Mas Ayu; Abdul Samat, Syafiq; Suroya, Suhaiza Hanim (Universiti Teknologi MARA, Kedah, 2018)
Many problems and difficulties in learning can be detected at the early learning process through the reading, spelling and identifying the alphabets. These difficulties in learning are known as Dyslexia, a disability in learning in children, which can be detected earlier if the children are sent to pre-school for early education at the age of 5 years or below.